2012
DOI: 10.1016/j.jcrs.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Intracameral cefuroxime injection at the end of cataract surgery to reduce the incidence of endophthalmitis: French study

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 33 publications
3
43
2
2
Order By: Relevance
“…Curiously, the postoperative endophthalmitis rate in patients without intracameral cefuroxime in these 3 studies was 0.32% (13/3990), 20 0.59% (39/6,595), 21 and 1.24% (35/2,826). 27 These rates are higher than in Group 1 in our study (0.155 % [12 of 7756]). We believe our study did not show a significant difference in endophthalmitis rate in patients who received intracameral cefuroxime because of the lower rate of preexisting endophthalmitis.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Curiously, the postoperative endophthalmitis rate in patients without intracameral cefuroxime in these 3 studies was 0.32% (13/3990), 20 0.59% (39/6,595), 21 and 1.24% (35/2,826). 27 These rates are higher than in Group 1 in our study (0.155 % [12 of 7756]). We believe our study did not show a significant difference in endophthalmitis rate in patients who received intracameral cefuroxime because of the lower rate of preexisting endophthalmitis.…”
Section: Discussioncontrasting
confidence: 61%
“…[19][20][21]27 The prospective randomized multicenter ESCRS study 19,20 concluded that intracameral cefuroxime prophylaxis decreased the endophthalmitis risk by 5 times. Later, the Spanish study 21 concluded that intracameral cefuroxime decreased the risk for endophthalmitis from 0.59% to 0.043% (relative risk, 0.072; 27 also concluded in favor of cefuroxime prophylaxis. Curiously, the postoperative endophthalmitis rate in patients without intracameral cefuroxime in these 3 studies was 0.32% (13/3990), 20 0.59% (39/6,595), 21 and 1.24% (35/2,826).…”
Section: Discussionmentioning
confidence: 99%
“…50 A French study of more than 5000 patients undergoing cataract surgery found the rate of endophthalmitis in patients receiving intracameral cefuroxime (1mg in 0.1ml) to be 0.044% as compared to 1.238% in patients not receiving the drug. 51 Similar results have been obtained in studies using intracameral cefazolin (1mg or 2.25mg per 0.1ml) at the end of cataract surgery. 52,53 An eleven year study in more than 50000 Asian patients by Tan et al reported a decrease in the rate of endophthalmitis from 0.064% to 0.010% after the addition of 1mg in 0.1ml intracameral cefazolin.…”
Section: Intracameral Antibioticssupporting
confidence: 78%
“…[4][5][6][7][8][9][10][11][12] Both the 2011 American Academy of Ophthalmology (AAO) Cataract Preferred Practice Pattern Guidelines and a 2011 ASCRS Cataract Clinical Committee review of endophthalmitis prevention noted that there was stronger evidence supporting direct intracameral injection than for any other method of antibiotic prophylaxis. 13,14 In 2013, 15 the ESCRS published endophthalmitis prophylaxis guidelines that reviewed the evidence supporting the safety and efficacy of direct intracameral injection of cefuroxime.…”
mentioning
confidence: 99%